La política criminal en Venezuela: especial referencia a la conflictividad social en torno al delito de secuestro - Añez Castillo, María Alejandra (Política criminal, 2011)
Criminal policies are conceived as a section of public policies destined to the planning, execution and control of preventive and repressive limits in the fight against criminality. This documentary-descriptive investigation outlines how in Venezuela, real criminal policies have not been formulated. For this reason, the answers to the criminal phenomenon have been lacking in coherence and have consisted of spasmodic answers to certain events and the anti-kidnapping policy does not escape this reality. Neither a policy nor a clear long-term strategy regarding kidnapping exist, the magnitude of the national information system is unknown, the lack of coordination between the security agencies, the dispute between the different competent organisms, these are some of the barriers faced by the State and which simultaneously are an advantage for both common and organized crime. Overcoming these obstacles begins by showing true political will; generating concrete, accurate, planned and pertinent actions concerning public governmental policies in all their aspects, without sole reference to the penal system.